Circular RNA Expression for Dilated Cardiomyopathy in Hearts and Pluripotent Stem Cell–Derived Cardiomyocytes - Zhang, Yiyu; Huang, Guoqing; Yuan, Zhaohu; Zhang, Yonggang; Chang, Rong (Frontiers in Cell and Developmental Biology, 2021)
Dilated cardiomyopathy (DCM) is a type of heart disease delimited by enlargement and dilation of one or both of the ventricles along with damaged contractility, which is often accompanied by the left ventricular ejection fraction (LVEF) less than 40%. DCM is progressive and always leads to heart failure. Circular RNAs (circRNAs) are unique species of noncoding RNAs featuring high cell-type specificity and long-lasting conservation, which normally are involved in the regulation of heart failure and DCM recently. So far, a landscape of various single gene or polygene mutations, which can cause complex human cardiac disorders, has been investigated by human-induced pluripotent stem cell (hiPSC) technology. Furthermore, DCM has been modeled as well, providing new perspectives on the disease study at a cellular level. In addition, current genome editing methods can not only repair defects of some genes, but also rescue the disease phenotype in patient-derived iPSCs, even introduce pathological-related mutations into wild-type strains. In this review, we gather up the aspects of the circRNA expression and mechanism in the DCM disease scenario, facilitating understanding in DCM development and pathophysiology in the molecular level. Also, we offer an update on the most relevant scientific progress in iPSC modeling of gene mutation–induced DCM.